Mit Investitionen und Industriepolitik aus der Stagnations- und Abhängigkeitsfalle - Sebastian Dullien (Wirtschaftsdienst, 2025)
– The next German government faces unprecedented challenges, with economic stagnation and shifting geopolitical landscapes threatening the country's growth model and sovereignty. The German economy, traditionally reliant on exports to China and the United States, faces mounting pressures from China's industrial policy and U.S. protectionism. Rising energy prices and geopolitical instability further exacerbate the situation. Policy responses must include a multi-year investment agenda, an active industrial policy, energy price stabilisation, and a reform of the constitutional debt brake to overcome stagnation, secure prosperity and strengthen economic resilience in a rapidly changing global environment.
Keywords: E61; F52; L52; 330; Wirtschaftspolitik; Industriepolitik; Deutschland; Wirtschaftspolitik; Industriepolitik; Deutschland